Impacts of respiratory phase shifts on motion‐tracking accuracy of the CyberKnife Synchrony™ Respiratory Tracking System. Issue 9 (17th July 2019) - Akino, Yuichi; Shiomi, Hiroya; Sumida, Iori; Isohashi, Fumiaki; Seo, Yuji; Suzuki, Osamu; Tamari, Keisuke; Otani, Keisuke; Higashinaka, Naokazu; Hayashida, Miori; Mabuchi, Nobuhisa; Ogawa, Kazuhiko
Abstract : Purpose: The Synchrony TM Respiratory Tracking System (SRTS) component of the CyberKnife ® Robotic Radiosurgery System (Accuray, Inc., Sunnyvale CA) enables real‐time tracking of moving targets by modeling the correlation between the targets and external surrogate light‐emitting diode (LED) markers placed on the patient's chest. Previous studies reported some cases with respiratory phase shifts between lung tumor and chest wall motions. In this study, the impacts of respiratory phase shifts on the motion‐tracking accuracy of the SRTS were investigated. Methods: A plastic scintillator was used to detect the position of the x‐ray beams. The scintillation light was recorded using a camera in a dark room. A moving phantom moved a U‐shaped frame on the scintillator with a 4th power of sinusoidal functions. Three metallic markers for motion tracking and four fluorescent tapes were attached to the frame. The fluorescent tapes were used to identify phantom position and respiratory phase for each video frame. The beam positions collected, when considered relative to the phantom motion, represent the degree of tracking error. Beam position was calculated by adding error value to phantom position. Motions with respiratory phase shifts between the target and an extra stage mimicking chest wall motion were also tested for LED markers. Log files of the SRTS were analyzed to evaluate correlation errors. Results: When target and LED marker motions were synchronized with a respiratory cycle of 4 s, the maximum tracking errors for 90% and 95% of beam‐on time were 1.0 mm and 1.2 mm, respectively. The frequency of tracking errors increased when LED marker motion phase preceded target motion. Tracking errors that corresponded to 90% beam‐on time were within 2.4 mm for 5–15% of phase shifts. In contrast, the tracking errors were very large when the LED marker delayed to the target motions; the maximum errors of 90% beam‐on time were 3.0, 3.8, and 7.5 mm for 5%, 10%, and 15% of phase shifts, respectively. The patterns of the tracking errors derived from the scintillation light were very similar to those of the correlation data of the SRTS derived from the log files, indicating that the tracking errors caused mainly due to the errors in modeling the correlation data. With long respiratory cycle of 6 s, the tracking errors were significantly decreased; the maximum tracking errors for 95% beam‐on time were 1.6 mm and 2.2 mm for early and delayed LED motion. Conclusion: We have investigated the motion‐tracking accuracy of the CyberKnife SRTS for cases with the respiratory phase shift between the target and the LED marker. The maximum tracking errors for 90% probability were within 2.4 mm when the target delays to the LED markers. When LED marker delays, however, very large tracking errors were observed. With a long respiratory cycle, the tracking errors were greatly improved to less than 2.2 mm. Coaching slow breathing will be useful for accurate motion tracking radiotherapy.